Relationship between Sensory Integration, Postural Stability and Fall Risk Assessment Parameters Using Physical Therapy for Individuals after Traumatic Brain Injury - Ugnė Buraitytė; Eglė Lendraitienė (Lithuanian Sports University, 2019)
Research background. Equilibrium and posture impairment is a common cause of collapse in individuals experiencing traumatic brain injury, which limits patient autonomy and independence in daily activities. Therefore, the recovery of balance is one of the primary goals of rehabilitation for individuals following the traumatic brain injury (Llorens et al., 2013). The aim was to determine the relationship between sensory integration, postural stability and fall risk assessment parameters using physiotherapy for individuals with traumatic brain injury. Methods. The study involved 16 people with traumatic brain injury. The subjects were divided into two groups - the frst one (n = 8) and the second one (n = 8). The frst group was taking 30 minutes regular physiotherapy and 30 minutes balance training with Biodex Balance System, second group - 30 min. regular physiotherapy and 30 minutes regular exercises for balance. Results. Changes in the postural stability index, anterior /posterior and medial/ lateral ﬂuctuation indexes, fall risk stability index and clinical sensory integration test index in both groups did not change statistically signifcant (p > 0.05). A strong, statistically signifcant direct relationship was found in the frst study group between the postural stability index and the ﬂuctuation of the anterior /posterior index changes (r = 0.922; p = 0.001). Conclusions. Physiotherapy using the Biodex Balance System and the usual physiotherapy is equally eﬀective in developing postural stability, sensory integration, and fall risk. The link between many of the studied indicators shows that postural stability, sensory integration and the risk of falls are related. Keywords: traumatic brain injury, sensory integration, postural stability, fall risk, physiotherapy.